Life and creativity Qavam ad-Din al-Itkani - Чухaнов С. (Journal of Oriental Studies, 2017)
The article describes the religious works Kavam ad-Din al-Itkani, who was born in the end of VII century in the city of Itkan in Kazakhstan. As well as an overview of biography author and discussed the value of his work.